Resilience In Those Who Have Broken Home: Resiliensi Pada Remaja Yang Mengalami Broken Home - Berlian Nur; Ririn Dewanti D (Academia Open, 2021)
This study aims to describe the aspects and factors of resilience of adolescents who experience a broken home in Sidoarjo. Aspects and factors that emerge help adolescents find the strength to accept and live their lives like teenagers in general. This research method is qualitative by using three adolescent subjects male and female aged 15-17 years. The data collection method used is interviews which are equipped with general guidelines and field notes. The results showed that each individual had aspects of motion regulation, impulse control, optimism, empathy, analysis of the causes of problems, self-efficacy, increased positive aspects and brought up social support resilience factors, cognitive skills, psychological resources so that they were able to accept.